DESAIN STRATEGI “COVI SRONDOL” DALAM RANGKA AKSELERASI JAWA TENGAH CORPORATE UNIVERSITY - SETIJOWATI, HARINI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
The results of competency development (bangkom) need to be monitored and evaluated for their benefits and impacts. There is already a post-training evaluation policy, but there is no monitoring instrument yet. Most of the implementation of monitoring and evaluation (monev) has not yet reached the impact. This is also one of the duties of the widyaiswara, namely being involved in ensuring the quality of bangkom. The purpose of the study was to design a post-bangkom monev strategy as an acceleration of Jateng Corpu. With a mixed method quantitative and qualitative research approach simultaneously, starting from data collection to analysis from Indrawan, Yaniawati, and Sugiyono. Although most informants do not understand Jateng Corpu, >50% believe that post-bangkom monev is an acceleration of Jateng Corpu. Considering these results and inputs, the design is packaged into the E-Panduan COVI Srondol (Collaboration for monitoring and eValuation post-competency development, is a Strategy, supported by Information and technology, was born in SRONDOL). So this study has implications for theory, practice, and subsequent research. Based on the results of the study, it can be concluded that the design of the post-bangkom monitoring and evaluation strategy is an important part of the implementation of Jateng Corpu which has been prepared in the form of an E-COVI Srondol Strategy Guide, consisting of an introduction, COVI Srondol Strategy, Mechanism, SOP, Risk Management, Closing and equipped with videos to facilitate its implementation. ABSTRAKHasil pengembangan kompetensi (bangkom), perlu dimonitoring dan dievaluasi manfaat serta dampaknya. Sudah ada kebijakan evaluasi pasca pelatihan, tetapi belum ada instrumen monitoringnya. Sebagian besar pelaksanaan monitoring dan evaluasi (monev) belum sampai pada dampak. Hal ini juga menjadi salah satu tugas widyaiswara, yaitu terlibat penjaminan mutu bangkom. Tujuan penelitian adalah mendesain strategi monev pascabangkom sebagai akselerasi Jateng Corpu. Dengan pendekatan penelitian campuran (mixed method) kuantitatif dan kualitatif secara bersamaan, mulai dari pengumpulan data sampai analisisnya dari Indrawan, Yaniawati, dan Sugiyono. Walaupun sebagian besar informan belum memahami Jateng Corpu, namun >50% meyakini bahwa monev pascabangkom merupakan percepatan Jateng Corpu. Memerhatikan hasil tersebut dan masukan-masukannya, desain dikemas menjadi E-Panduan COVI Srondol (Collaboration for mOnitoring and eValuation post-competency development, is a Strategy, supported by Information and technology, was born in SRONDOL). Maka penelitian ini telah memiliki implikasi teori, praktik, dan penelitian berikutnya. Berdasar hasil penelitian tersebut dapat disimpulkan bahwa desain strategi monev pascabangkom menjadi bagian penting dalam implementasi Jateng Corpu telah disusun dalam bentuk E-Panduan Strategi COVI Srondol, terdiri dari pendahuluan, Strategi COVI Srondol, Mekanisme, SOP, Manajemen Risiko, Penutup dan dilengkapi video untuk memudahkan implementasinya.